CLIL in Colombia: Challenges and Opportunities for its Implementation. - Mosquera Pérez, Jhon Eduardo (GIST – Education and Learning Research Journal, 2022)
CLIL “Content and Language Integrated Learning” is an approach that has been gaining momentum in applied linguistics within the last few years. Although at first its implementation might appear to be something simple, as there is a tendency to think that for the successful application of CLIL based lessons it is only necessary to impart classes in English, in fact, there is a series of elements that language teachers and scholars should be take into consideration before reducing such an innovative approach to that simplistic view. Hence, in this reflective article I address some of the challenge and opportunities that may arise when implementing this innovative metho to language teaching with an especial emphasis on the Colombian context. Within the context of this reflective article, firstly I present a general theorization of the CLIL approach. Secondly, I reflect on three of the challenges as well as on three the opportunities for the implementation of said approach in our national context. Finally, I present the conclusions.